Filterisasi Informasi Melalui Literasi Media: Upaya Indentifikasi Berita Hoak Melalui Media Sosial - Juhari Juhari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Everyone needs a variety information in their life, so they upload various content through social media. However, not all information presented in the media contains elements of truth. Hoax is still a serious problem that can harm media users get caught up. This research aims to identify several characteristics of fake news spread on social media so that people can avoid various cybercrimes. This research uses a qualitative descriptive approach by collecting a number of sources both through journals and social media that contain of hoax in order to obtain data. The Theory of Media Setting is used as a guide for analyzing the content. The research results show that there are still many Indonesian people who do not have adequate knowledge in identifying the characteristics of fake news on social media, especially lower middle class people who are not able to filter information so they are still often trapped in the media settings. In the other side, the people, especially middle and upper educated groups, are able to differentiate between true and fake news.